Chronic cerebral ischemia and headache in patients in primary care physician's practice - V. N. Shishkova; T. V. Adasheva (Неврология, нейропсихиатрия, психосоматика, 2021)
Today, chronic cerebral ischemia (CCI) is the most common diagnosis in our country, both in neurological and general medical practice. The high frequency of comorbid conditions and diseases predisposing to the development of CCI, and the association with the risk of stroke and dementia, which increase patient disability, make CCI an urgent medical and social problem. Proper diagnosis of CCI allows the prescription of effective treatment, prevents the disease progression, and the development of strokes and dementia. The article deals with the treatment principles for elderly and senile patients with headache and CCI in outpatient practice. It discusses the causes of headache in CCI patients and its treatment methods. It also covers in depth the spectrum of therapeutic effects of Neurox® (ethylmethylhydroxypyridine succinate) and Neupilept® (citicoline) in this category of patients.